Exploring the Educational Potential of Mutualistic Interaction between Cynometra cauliflora and Arbuscular Mycorrhiza in PT Chandra Asri’s Biodiversity Park: A Content Analysis for High School Biology Learning - Firdaus, Najmi; Rachmawati, Dian; Khastini, Rida Oktorida; Fitri, Siti Gia Syauqiyah; Amelia, Evi; Fitriana, Desi Eka Nur; Survani, Rifki; Wahyuni, Indria (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Arbuscular mycorrhizal fungi (AMF) form mutualistic interactions with plants, including Cynometra cauliflora (Namnam), a tropical indigenous species from the Fabaceae family. This study explores the educational potential of this biological relationship to enrich high school biology education under the Kurikulum Merdeka framework. Field research was conducted at PT Chandra Asri’s Biodiversity Park in Cilegon, Banten Province, Indonesia, an area with rich local biodiversity and a tropical rainforest climate. The study used a qualitative content analysis approach following an exploratory-descriptive model. Nine naturally growing C. cauliflora individuals were selected for morphological observations and root sampling. Morphological characteristics were documented following standard botanical protocols, while AMF colonization was assessed through root clearing, Phillips and Hayman staining method, and microscopic observation. The percentage of AMF colonization was calculated using the gridline intersect method. Habitat characterization to understand the ecological context. Curriculum analysis reviewed Indonesian biology standards, textbooks, and scientific literature to map potential integrations. Key concepts such as mutualism, nutrient cycling, biodiversity conservation, and plant physiology were identified for curriculum enrichment. The findings suggest that studying C. cauliflora and its AMF association can effectively support Capaian Pembelajaran (Learning Achievement Targets), fostering student skills in scientific methods, environmental awareness, and critical thinking. Incorporating local examples promotes contextual and inquiry-based learning, aligning with the spirit of the Kurikulum Merdeka and strengthening students’ ecological literacy. In conclusion, the mutualistic relationship between C. cauliflora and AMF offers a valuable, locally relevant scientific model for enhancing biology education. It bridges scientific knowledge, cultural understanding, and sustainability, preparing students for real-world ecological challenges.